PEMBANGUNAN EKONOMI BERWAWASAN GENDER. MASIHKAH BERLAKU DI ERA REVOLUSI INDUSTRI 4.0 (SEBUAH PERSPEKTIF SOSIAL EKONOMI) - Abdulharis Tamalene; Sally Paulina Sandanafu; Marcha S.I. Matitaputty (Jurnal Inovasi Penelitian, 2021)
This research aims to explore the phenomena that occur related to the role and problematic of women in development, especially in Maluku province. This research is a qualitatively descripted study using observation and interview methods supported by secondary data to support of research data. The informants in this study were women who belonged to women's organizations namely IWAPI Maluku province, organizations among ordinary housewives (PKK) and merchant women who had their own businesses (women enterpreuner) in Ambon city. This research proves that gender inequality still exist in development process thus,women can give positive contribution to a local and central governments in order to succeed an economic development programs particularly in gender minded and become a consideration for local and central governments in drafting policies and strategic decision-making related to the role of women in gender-minded development in the era of the 4.0 industrial revolution.